On greenhouse gas emissions and thermal efficiency of natural gas/diesel dual-fuel engine at low load conditions: Coupled effect of injector rail pressure and split injection. (15th May 2019) - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid; Liko, Brian
Highlights: Coupled effects of diesel split injection and rail pressure on NDDF is studied. Split injection of NDDF significantly reduces NOx even at high P-rail. GHG of NDDF with split injection is reduced compared to single injection. NDDF with split injection has a higher thermal efficiency than single injection. Abstract: Replacing diesel by natural gas in diesel engine is of great interest for transportation and power station industry due to larger availability and lower environmental impact of natural gas compared to diesel fuel. However, natural gas/diesel dual-fuel (NDDF) engine has lower thermal efficiency and produces higher greenhouse gas (GHG) emissions than its counterpart diesel engine at low load conditions when conventional diesel combustion strategy is used. In order to overcome this drawback, the present paper experimentally and numerically investigates the coupling of two strategies; namely increasing diesel injection rail pressure and splitting diesel injection of a heavy-duty NDDF engine at low engine load conditions. The results revealed that increasing the injection rail pressure decreases thermal efficiency of the NDDF engine with split injection as a result of overly advanced combustion phasing. However, a higher thermal efficiency (37.2%), than that of the diesel-only and the NDDF engine with a single injection, can be achieved under optimized combustion phasing. Increasing the injection rail pressure significantly reduces the unburned methane emissions of the NDDF engine with split injection, especially at lower split ratios (mass of the injected diesel in the first pulse divided by that of the total injected diesel). However, increasing the injection rail pressure does not affect the unburned methane emissions under a split ratio of 65%. This is due to the fact that a larger portion of diesel fuel impinges onto the cylinder wall surface as revealed by the simulation results. The optimum methane emissions of the NDDF engine with split injection is reduced by 50% compared to the best condition of the NDDF engine with a single injection. Moreover, the indicated specific carbon dioxide equivalent (ISCO2-equivalent) emissions of the NDDF engine with split injection are reduced by 11% compared to those of the NDDF engine with a single injection and diesel-only engine. All in all, the present study demonstrated that thermal efficiency and GHG emissions of the NDDF engine can be further improved when simultaneously varying diesel fuel injection split ratio and rail pressure increase. This strategy is also found to help reducing pressure rise rate (PRR) and NOx and soot emissions.